A new species of Metabelbella (Acari: Oribatida: Damaeidae) from Quercus forests of southern Portugal - Ermilov, Sergey G.; Shtanchaeva, Umukusum Y.; Subías, Luis S. (International Journal of Acarology, 2012)
In the course of studies of the oribatid fauna of oak forests from southern Portugal, we found representatives of 60 species (51 genera and 38 families) of which 39 species are registered for the first time for Portugal. One new species, Metabelbella epidamaeiformis sp. nov., is described. It is clearly distinguishable from all other species of the genus by the presence of spinae adnatae. An identification key to known Iberian species of Metabelbella is presented. A checklist, the locality and the distribution of all oribatid taxa recorded by us are presented.
doi: 10.1080/01647954.2011.645284doi: 10.1080/01647954.2011.645284The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: checklist; fauna; key; Metabelbella; new species; Oribatida; Portugal; Quercus forests